2004
DOI: 10.1023/b:bile.0000032962.79531.fd
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan sponges as tissue engineering scaffolds for bone formation

Abstract: Rat calvarial osteoblasts were grown in porous chitosan sponges fabricated by freeze drying. The prepared chitosan sponges had a porous structure with a 100-200 microm pore diameter, which allowed cell proliferation. Cell density, alkaline phosphatase activity and calcium deposition were monitored for up to 56 d culture. Cell numbers were 4 x 10(6) (day 1), 11 x 10(6) (day 28) and 12 x 10(6) (day 56) per g sponge. Calcium depositions were 9 (day 1), 40 (day 28) and 48 (day 56) microg per sponge. Histological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(134 citation statements)
references
References 12 publications
6
123
0
4
Order By: Relevance
“…[53][54][55][56] The majority of these studies do not show mineralization data from cell-free controls. As seen in this study, although chitosan is clearly highly biocompatible and osteoconductive, 40,57,58 the osteoinductive potential of this particular ionotropic biomaterial should not be evaluated only by the calcium deposition.…”
Section: +mentioning
confidence: 99%
“…[53][54][55][56] The majority of these studies do not show mineralization data from cell-free controls. As seen in this study, although chitosan is clearly highly biocompatible and osteoconductive, 40,57,58 the osteoinductive potential of this particular ionotropic biomaterial should not be evaluated only by the calcium deposition.…”
Section: +mentioning
confidence: 99%
“…From a tissue-engineering perspective, induction of an antiinflammatory pro-regenerative macrophage phenotype is of key relevance, as reparative macrophages are crucial in tissue remodeling after inflammation, guiding the host response to implanted biomaterials. Thus, the claim that Ch may be an adequate material for tissue-engineering applications, such as in bone repair, 11,50 may be related to its ability to modulate the inflammatory response. Moreover, besides supporting attachment and proliferation of osteoblastic cells, 16,51 Ch also drives macrophage production of soluble mediators involved in bone physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chitosan membrane (10), nanofiber (11), and sponge (12) have been produced as tissue-engineering scaffolds for bone formation. However, chitin (chitosan) changes its physical and biological properties according to its deacetylation level (13).When mouse osteoblast cells were cultured on sheets made of nondeacetylated chitin, and 35, 50, and 70% deacetylated chitin (DAC-0, DAC-35, DAC-50, and DAC-70, respectively), DAC-35 had the highest effect of growth and differentiation of the cells, and DAC-50 and DAC-0 had intermediate effects, while DAC-70 suppressed the growth and differentiation of the cells (13).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of rotary blood pumps on coronary blood flow have not been adequately documented; one study showed a decrease in the coronary flow in pigs with and without a surgically created coronary stenosis (11). Improved perfusion has been previously registered with the use of pulsatile pump systems (12). New information about coronary perfusion and myocardial oxygen consumption is THOUGHTS AND PROGRESS 77…”
Section: Coronary Hemodynamics and Myocardialmentioning
confidence: 99%